Early versus late discharge from hospital after open appendectomy - Krismanuel, Hari (Faculty of Medicine, Trisakti University, 2010)
To date there is increasing pressure on surgeons to minimize the time that the patient stays in hospital. Patients with acute appendicitis without perforation or peritonitis are not discharged early due to concern on the part of the surgeon that it would increase surgical wound infection rates. The aim of this study was to compare surgical wound infection rates after open appendectomy (OA) of patients with acute appendicitis without perforation or peritonitis in an early discharge (ED) group and a control group without early discharge (late discharge [LD] group. The study was also to evaluate patient acceptance of ED in comparison to the LD group. A cross sectional study was carried out on adult patients (age >14 years) with acute appendicitis without perforation or peritonitis, who underwent open appendectomy. The results showed that there was no significant difference (p>0.05) in surgical wound infection rates in both the intervention (ED) and control (LD) groups. In addition, there was a significant difference (p<0.05) in patient acceptance (satisfaction) in both groups, where patients in the ED group were more satisfied than the patients who had not been discharged early. The conclusions of this study are that early discharge from hospital after open appendectomy does not increase surgical wound infection rate and has good patient acceptance.